Cost‐effectiveness of Quantitative Pretest Probability Intended to Reduce Unnecessary Medical Radiation Exposure in Emergency Department Patients With Chest Pain and Dyspnea. (21st April 2015) - Troyer, Jennifer L.; Jones, Alan E.; Shapiro, Nathan I.; Mitchell, Alice M.; Hewer, Ian; Kline, Jeffrey A.; Mark Courtney, D.
Abstract Objectives Quantitative pretest probability (qPTP) incorporated into a decision support tool with advice can reduce unnecessary diagnostic testing among patients with symptoms suggestive of acute coronary syndrome (ACS) and pulmonary embolism (PE), reducing 30‐day costs without an increase in 90‐day adverse outcomes. This study estimates long‐term (beyond 90‐day) costs and outcomes associated with qPTP. The authors hypothesized that qPTP reduces lifetime costs and improves outcomes in low‐risk patients with symptoms suggestive of ACS and PE. Methods This was a cost‐effectiveness analysis of a multicenter, randomized controlled trial of adult emergency patients with dyspnea and chest pain, in which a clinician encountering a low‐risk patient with symptoms suggestive of ACS or PE conducted either the intervention (qPTP for ACS and PE with advice) or the sham (no qPTP and no advice). Effect of the intervention over a patient's lifetime was assessed using a Markov microsimulation model. Short‐term costs and outcomes were from the trial; long‐term outcomes and costs were from the literature. Outcomes included lifetime transition to PE, ACS, and intracranial hemorrhage (ICH); mortality from cancer, ICH, PE, ACS, renal failure, and ischemic stroke; quality‐adjusted life‐years (QALYs); and total medical costs compared between simulated intervention and sham groups. Results Markov microsimulation for a 40‐year‐old patient receiving qPTP found lifetime cost savings of $497 for women and $528 for men, associated with small gains in QALYs (2 and 6 days, respectively) and lower rates of cancer mortality in both sexes, but a reduction in ICH only in males. Sensitivity analysis for patients aged 60 years predicted that qPTP would continue to save costs and also reduce mortality from both ICH and cancer. Use of qPTP significantly reduced the lifetime probability of PE diagnosis, with lower probability of death from PE in both sexes aged 40 to 60 years. However, use of qPTP reduced the rate of ACS diagnosis and death from ACS at age 40, but increased the death rate from ACS at age 60 for both sexes. Conclusions Widespread use of a combined qPTP for both ACS and PE has the potential to decrease costs by reducing diagnostic testing, while improving most long‐term outcomes in emergency patients with chest pain and dyspnea.